Pengaturan mengenai Tenaga Kerja Asing dan Prinsip Non-Diskriminasi di Masyarakat Ekonomi ASEAN (AEC) berdasarkan Kewarganegaraan - Sirait, Yohanes Hermanto; Permatasari, Ai (UIR Law Review, 2018)
Abstract Every country has an obligation to ensure job vacancies for its people, so the priority of local workers is preferred to do. However, with the enactment of ASEAN Economic Community (AEC) in early 2016 in ASEAN, every country bound to open more opportunities for foreign workers to work in all ASEAN states. This agreement may bring into a contravention between national policies to accentuate local worker with obligation of free flow of workers in ASEAN, especially occupation regulated on Mutual Recognition Arrangements (MRAs). This article examines the regulation for foreign worker and the implementation of non-discrimination principle based on nationality in AEC. This is particularly pertinent considering a state’s role to ensure stability of foreign worker and fruitfulness of AEC. Ultimately, this Article argues all ASEAN states should embrace harmonization as the new standard for foreign worker under MRAs. Keywords: ASEAN Economic Community; Foreign Worker; Nationality; Principle of Non-Discrimination